1992
DOI: 10.1063/1.858365
|View full text |Cite
|
Sign up to set email alerts
|

Transverse flow over a wavy cylinder

Abstract: Transverse flow over a wavy cylinder was investigated experimentally; surface-pressure distributions and flow visualizations were obtained for a set of wavy cylinders with different axial wavelengths. Significant spanwise pressure gradients were present, resulting in three-dimensional separation lines and the formation of streamwise trailing vortex structures near the geometric nodes. Despite the symmetry of the geometries, the separated flow structures near the geometric nodes were distinctly asymmetric a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 5 publications
4
45
0
Order By: Relevance
“…Ahmed & Bays-Muchmore (1992) and Ahmed, Khan & Bays-Muchmore (1993) investigated experimentally the pressure field and flow patterns over a wavy cylinder. Lam et al (2004a) and Lam, Wang & So (2004b) performed experiments to deal with the drag reduction and the relevant flow-induced vibration for different wavy cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed & Bays-Muchmore (1992) and Ahmed, Khan & Bays-Muchmore (1993) investigated experimentally the pressure field and flow patterns over a wavy cylinder. Lam et al (2004a) and Lam, Wang & So (2004b) performed experiments to deal with the drag reduction and the relevant flow-induced vibration for different wavy cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…The wavy trailing edge used by Tombazis and Bearman 10 caused vortex splitting in the wake due to the phase mismatch between two neighboring cells of different shedding frequencies. In the work with wavy circular cylinders, 8,9,12,13 the three-dimensionality was caused by differences in the flow characteristics between the nodal and saddle planes. Lam et al 12 observed that the wake in the formation region of the saddle plane was wider than that of the nodal plane.…”
Section: B Spanwise Forcingmentioning
confidence: 99%
“…Some researchers [7][8][9][10][11][12][13][14] created a geometric boundary condition that varied in the spanwise direction, with the goal of influencing the global wake dynamics. Park et al 7 concluded that variation of the wake width in the spanwise direction forced the Kármán vortex street to lose its twodimensional nature and thus led to vortex dislocations and reduced drag.…”
Section: B Spanwise Forcingmentioning
confidence: 99%
“…증되었다 (Ahmed and Bays-muchmore, 1992;Nebres et al, 1993;Chyu and Rockwell, 1996;Lam et al, 2004a;Lam et al, 2004b;Lee and Nguyen, 2007;Lam and Lin, 2008 (Unal and Rockwell, 1988;Prasad and Williamson, 1997;Norberg, 1998, Dong et al, 2006 (Breuer, 1998;Breuer, 2000;Jordan and Ragab, 1998;Jordan, 2002). (Keefe, 1962;Bishop and Hassan, 1964;White, 1974;Moeller, 1982;Moeller and Leehey, 1984;Norberg, 1987;Tadrist et al, 1990;Gopalkrishnan 1993 있다 (Unal and Rockwell, 1988;Prasad and Williamson, 1997;Norberg, 1998, Dong et al, 2006.…”
Section: 서 론mentioning
confidence: 99%
“…
ABSTRACT: We investigated the Reynolds number effects on the flow over a twisted offshore structure in the range of -muchmore, 1992;Nebres et al, 1993;Chyu and Rockwell, 1996;Lam et al, 2004a;Lam et al, 2004b;Lee and Nguyen, 2007;Lam and Lin, 2008
…”
mentioning
confidence: 99%